Obesity-Induced Mechanisms in Colorectal Cancer Development: A Narrative Review - Sahu, Pranamita; Dubey, Debasmita; Panda, Soumya Surath; Tripathy, Subrat Kumar (AL-Kindy College Medical Journal, 2025)
Obesity is a significant risk factor for colorectal cancer (CRC), influencing its development through multiple biological pathways. Elevated levels of insulin, insulin-like growth factor-1 (IGF-1), leptin, resistin, and inflammatory cytokines such as interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) contribute to colonic cell proliferation and tumor formation. Additionally, obesity-induced hormonal imbalances, including decreased adiponectin and ghrelin, further increase CRC risk. Changes in gut microbiota due to obesity also play a role in carcinogenesis, highlighting the complex interplay between metabolic, inflammatory, and microbial factors. This review explores the pathophysiological mechanisms linking obesity to CRC, emphasizing its role as a modifiable risk factor. Insulin resistance, chronic inflammation, oxidative stress, and dysregulated adipokine secretion are key contributors to CRC progression in obese individuals. By analyzing molecular and epidemiological evidence, this review underscores the importance of early CRC screening for obese individuals, along with lifestyle modifications such as weight loss, dietary improvements, and increased physical activity. Furthermore, microbiome-targeted interventions, including probiotics and prebiotics, may help counteract obesity-driven dysbiosis and reduce CRC risk. Emerging biomarkers and therapeutic targets offer potential for developing obesity-specific CRC treatments. Given the rising global burden of CRC, integrating preventive healthcare strategies, public health initiatives, and clinical interventions is essential for reducing its incidence and improving patient outcomes. Addressing obesity through targeted preventive measures can significantly lower CRC-related morbidity and mortality, making it a crucial aspect of cancer prevention and management